Handling Tovey's Bach. Issue 3 (14th March 2022) - Phillips, Reuben
ABSTRACT: Adopting an approach inspired by the field of book history, this article examines a heavily annotated copy of the Bach-Gesellschaft edition that belonged to Donald Francis Tovey. Tovey's annotations mix scholarly acumen with witticism and wonderment, variously providing thoughts on performance practice, complaints about idiotic editors, personal memories of past performances, and penetrating critical commentary. I consider the affordances of this edition as a material object, reflecting on the new ways of being around Bach's music that it enabled. The later sections of the article suggest that Tovey's wider engagement with Bach's music might be viewed as a kind of resistance to the Gesellschaft edition's presentation of Bach's compositions as a series of ontologically stable musical works. As well as contributing new insights into Tovey's achievements, I demonstrate the value of a richer understanding of what might constitute 'score-based' engagement with music in the late nineteenth and early twentieth century.